Deskripsi Analisis Peran Wawasan Nusantara dan Pendidikan Agama dalam Upaya Pembangunan Karakter Bangsa Indonesia di Era Kontemporer - Galbani Fadilah; Busro Busro (Journal of Society and Development, 2022)
The character and paradigm of the Indonesian nation in the contemporary era is experiencing many problems, one of which is the birth of the paradigm group of the liberal Indonesian society (MIL), the structuralist Indonesian society (MIS) and the marginalist Indonesian society (MIM) which later gave birth to implicit social inequality. Therefore, this study aims to discuss the three contemporary paradigms and their problems which are then combined with the insight of the archipelago and religious education to find solutions and their handling in efforts to build the character of the Indonesian nation in the contemporary era. This research uses qualitative methods through literature study as well as philosophical and sociological analysis of the phenomena that occur. The results of this study indicate that the insight of the archipelago and also religious education is an ideal solution in overcoming the problems of the Indonesian nation's paradigm in the contemporary era and has a central role in the development of the character of the Indonesian nation if its implementation can be maximized by means of character education which is as it should be.